Enhancing EFL Speaking Skill Through Student Mobility Program (Case of Non English Department Students) - Rahmawati, Amalia; Nur Syafiq, Ahmad; Anwari, Anwari; Isnina, Fathimah (Konsorsium Lembaga Penelitian dan Pengabdian kepada Masyarakat Perguruan Tinggi Muhammadiyah 'Aisyiyah (PTMA) Koordinator Wilayah Jawa Tengah - DIY, 2021)
Internalization program especially student mobility program incampus is important not only to improve the quality of the campusbut also to improve the students’ quality. By joining the program, thestudent can learn many thing, such as culture, all about SDGs, ect.The main thing of the student mobility program is the EFL haschance to practice their skill to speaking during the program. Theprogram done virtually for 2 weeks. This research aims to describethe speaking improvement through student mobility program. Thisresearch belongs to pre-experimental design with pre-test and posttest. The population and sample is 10 students as the representativeof Indonesia campus, and the sampling technique used is totalsampling. The data was analysed statistically and provided thequalitative data to strength the research. There are five indicatorsthat have been improved, such as pronunciation, grammar,vocabulary, fluency, and comprehension. It can be concluded thatthere is a significant different before and after joining studentmobility program.